ETNOMATEMATIKA PADA ZAKAT MAL PERTANIAN DI DESA GUMUKSARI KALISAT JEMBER - Solihin, Moh Khoirus; Lutfiyah, Lutfiyah; Sujiwo, Dimas Anditha Cahyo (Universitas Insan Budi Utomo, 2025)
The aim of this research is to describe ethnomathematics in the agricultural mall zakat in Gumuksari Kalisat Jember village. Ethnomathematics is the study of how various cultural groups understand, organize, and use mathematical concepts in the context of everyday life. Mathematics in a cultural context can become more relevant and meaningful for society in general. The research method in this research is qualitative research. This research uses a qualitative descriptive method because the aim is to find out what mathematical aspects are contained in farmers' activities in calculating zakat mal in Gumuksari village. This research uses techniques in the form of observation and interviews. Based on the research results, it was found that the ethnomathematics contained in the process of implementing zakat mal on rice farming are reduction activities during grain milling, distribution activities during the process of transferring rice to traditional Budhek agricultural equipment, percentage activities when rice is collected in the Budhek for which zakat mal will be issued, and use of traditional Budhek agricultural tools that contain the concept of flat and spatial structures. It is concluded that ethnomathematics in agricultural zakat in Gumuksari Village, Kalisat, Jember cannot be separated from farming activities for farmers in the Gumuksari community, especially the mathematical thinking skills of male farmers.